ChemInform Abstract: Acylsilanes in Rhodium(III)‐Catalyzed Directed Aromatic C—H Alkenylations and Siloxycarbene Reactions with C—C Double Bonds. Issue 29 (22nd July 2014) - Becker, Peter; Priebbenow, Daniel L.; Pirwerdjan, Ramona; Bolm, Carsten
Abstract A Rh‐catalyzed ortho‐directed olefinations of aroylsilanes followed by light‐induced intramolecular cyclizations to indanone derivatives are described.